Ambivalence and paradox: the battered woman's interactions with the law and other helping resources - Labe, Dana (Rhodes University, Faculty of Humanities, Department of Sociology, 2001)
This thesis explores how the battered woman attachment to her abusive partner impacts on her interactions with the legal system and non-legal resources. This qualitative research project is based on in-depth interviews conducted with seven abused women who procured interdicts in terms of the Prevention of Family Violence Act 133 of 1993 to restrain their husbands from assaulting them. The research reviews the nature of abuse suffered by the participants, their psychological attachments to their husbands, and their patterns of help-seeking in relation to the law and non-legal resources. Two main theoretical frameworks, psychoanalysis and feminism inform this study. The study found that the participants retained unrealistic hopes that their husbands would reform and become loving, caring partners, and that they treated their husbands with care and sympathy despite their husbands' often brutal behaviour towards them. The findings suggest that the women's behaviour towards their husbands was the product of two reality distorting psychological defences, splitting and the moral defence which they used to preserve their attachments to their abusive partners. These defences intersected with rigid patriarchal prescriptions of femininity which dictate that women should be stoically caring towards their husbands, and should hold relationships together no matter what the cost to themselves. The participants interactions with the legal system and with non-legal sources of help were structured by their reliance on splitting and the moral defence, and by the dictates of patriarchal ideology. Whilst it is undoubtedly true that at one level the participants sought help to get protection from abuse, the study shows that their help-seeking was motivated by their conflicting desires to punish and reform their husbands. The participants sought help in ways which enabled them to strike a compromise between expressing their anger at their husbands, whilst simultaneously preserving their psychological attachments to them. The study concludes that the women's interactions with the law and with other helping resource reflect their attempts to preserve their paradoxical attachments to their husbands, and to stabilise their own fragile sense of self and gender identity.
Keywords: Family violence -- Law and legislation; Abused women; Family violence; Wife abuse; Women -- Crimes against; Women -- Counseling of; Family violence -- Prevention